Bilateral capacity is related to bilateral upper limb use after stroke: a study by behavioral maps, accelerometers and perceived amount of use - Vier C.* (2022)
© 2020 Informa UK Limited, trading as Taylor & Francis Group.Purpose: This study aimed to assess the following in individuals after stroke: (1) relationship between upper limb (UL) use by direct observation at home with use perceived and measured by accelerometers; (2) complementarity of these three measurements; and (3) relationship between UL bilateral capacity and bilateral use. Materials and methods: Thirty-one individuals with chronic hemiparesis participated in this cross-sectional study. UL use was assessed using a behavioral map (BM), the Motor Activity Log-Amount of Use (MAL-AOU), and accelerometers, while UL capacity was assessed using the Test d'Evaluation des Membres Supérieurs des Personnes Âgées (TEMPA). Results: The BM was strongly correlated with perceived use (MAL-AOU, ρ = 0.76) and accelerometer (ρ = 0.70). Bilateral UL use (BM) was moderately (ρ = 0.65) correlated with bilateral MAL-AOU and bilateral use by accelerometers (ρ = 0.62). The BM aided our understanding of how the paretic UL was used. The correlation between bilateral capacity (TEMPA bilateral) and bilateral use (BM) was significant (ρ = 0.49), while that with bilateral MAL-AOU and accelerometer were ρ = 0.68 and ρ = 0.50, respectively. Conclusion: A BM is a valid way to quantify UL use and can complement information assessed regarding perceived use and by accelerometers.Implications for rehabilitation Behavioral maps may be valuable to complement information assessed by perceived UL use and accelerometers. Quantifying bilateral capacity will reflect in a better understanding of actual paretic UL use after stroke. Accelerometers can underestimate the amount of paretic UL use in asymmetrical bilateral tasks.